Low-platinum catalyst based on sulfur doped graphene for methanol oxidation in alkaline media. (March 2021) - Vulcu, A.; Radu, T.; Porav, A.S.; Berghian-Grosan, C.
Abstract: A novel two-step, low-temperature method was employed for the synthesis of a catalyst with small platinum content (2 wt%) based on sulfur doped reduced graphene oxide (S-RGO-Pt ). Morphology and chemical composition of the hybrid material were investigated by several methods: X-ray powder diffraction (XRD), transmission and scanning electrode microscopy (TEM, SEM), elemental analysis, X-ray photoelectron spectroscopy (XPS) and Raman spectroscopy. The electrocatalytic performance of the prepared hybrid material was investigated in 1M CH3 OH/1M NaOH using a modified glassy carbon electrode (GC_S-RGO-Pt ). The results showed excellent electrocatalytic activity and stability toward methanol oxidation in alkaline media (50.4% activity retained after 500 cycles and 8.4% after 1000 cycles) compared to commercial platinum 10 wt% on carbon (Pt/C) material (8.09% activity retained after 500 cycles). The catalyst tolerance to CO poisoning intermediates was evaluated using CO stripping voltammetry and the ratio of forward and backward peak current density ( I f /I b ). The I f /I b ratio calculated for S-RGO-Pt is 15, while for Pt/C is 9.6, which clearly demonstrates that the prepared hybrid material is significantly more efficient than commercial Pt/C, even if the platinum content is only 2 wt%. The rotating disk electrode (RDE) technique was employed to study the kinetic aspects of methanol oxidation reaction in alkaline media. To follow the transformations occurred at the electrodes' surfaces after the electrochemical treatment, the Raman spectroscopy and Machine Learning (ML) algorithms were used; the results also indicated a greater stability of the S-RGO-Pt composite for Methanol oxidation reaction (MOR) in alkaline media. Graphical abstract: The hybrid material (S-RGO-Pt) has a wrinkled structure with an uniform distribution of the platinum nanoparticles and exhibits remarkable electrocatalytic performance both in terms of CO poisoning species tolerance and long-term stability. Image 1 Highlights: Low-platinum catalyst based on sulfur doped graphene (S-RGO-Pt) was prepared. The catalyst was tested as anode material for methanol oxidation in alkaline media. The S-RGO-Pt catalyst has outstanding electrocatalytic activity and stability. Machine Learning algorithms were employed to evaluate the electrodes' surfaces.